Stories from the edge - Hartley, Felicity (Department of Pathology, 2025)
Background: Discussing sexual health (SH) is often awkward and taboo due to societal and cultural factors. Sexually transmitted infections (STIs) and unintended pregnancies significantly impacts the health and lives of young women (YW). Visual arts-based approaches have been positively used for promoting embodied recall, overcoming language barriers to assist sensitive research and facilitate language-led data gathering. This participatory qualitative study investigates what the novel non-verbal painting process, Stories from the Edge (SFTE), brings to communication amongst a group of YW when talking about their sexual relationships and SH service seeking experiences. SFTE asks how it may enrich dialogues in in-depth interviews (IDIs) and focus group discussions (FGD). Method: Seven isiXhosa YW aged 21 -25 years were recruited to participate in a 6-11 session art-based study where they painted their SH experiences. The data set for the study included multiple large paintings, IDIs, an FGD, and informal discussions. All data including verbal discussions and interviews was recorded and translated where necessary, transcribed and thematically analysed. Results: The YW expressed that painting their SFTE provided an opportunity to express complex emotional experiences of intimate relationships which they found too hard to articulate verbally. Through the process they gained a deeper understanding of themselves and their emerging self-agency within their intimate relationships, and when accessing SH services. Inductive thematic analysis of verbal IDIs, FGD and informal discussions revealed key influences on communication about their intimate relationships and accessing SH services. Closer interpersonal relationships (family, partners, peers) emerged as the most significant contributors to their attitudes and practices, more than the socio-cultural (school and non-governmental organizations) or organizational (health care providers) spheres in their environment. As YW transitioned from adolescence to early adulthood, partners and friends assumed increasing importance. The desire for improved communication about sex, and relationships with those closest to them and when accessing SH services, was mediated by YW's confidence in their own self-agency and the power dynamics within these relationships. Conclusion: The SFTE visual art-based method facilitated the YW in recalling and voicing their SH experiences more comprehensively than language-only led research and promoted their own self-agency. The study underscores the importance of building communication skills of YW to enable them to speak confidently about their needs and desires within their intimate partnerships and when accessing SH service care.